The Profile of Patients Presented at Nephrology Opd With Obstructive Nephropathy; Single Centre Experience (Bangladesh Journal of Urology, 2020)
Introduction: Obstructive Uropathy which refers to the structural and functional change impeding the normal urine flow is one of the common cause of renal failure . It has diverse effect on normal renal function as well as there is also diversity on its etiology and outcomeMaterial & methods: Total 108 patients who came to Nephrology OPD with various degree of renal dysfunction resulting from Obstruction of Urinary tract was included in the study.Result : Among the patients 65% were male and their mean age was 51±13.5 years . Common clinical features were loin pain (41%) ; vomiting (30%) ; edema (26%) ; Oligourea (46%) & LUTS (19%). Common etiologies of Obstruction was BEP (28.7%);Urolithiasis(24%); Cervical malignancies(11%); Congenital abnormalities (13%) & stricture urethra(12%). About 37% patients had to under go RRT.Conclusion : Specific strategies to target improvements in early diagnosis renal recovery and patients survival are needed in this patient group.Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.132-135